2022
DOI: 10.3390/coatings12020241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Performance Characterization of Semi-Flexible Pavements

Abstract: Semi-flexible pavement (SFP) is made up of a porous skeleton of asphalt mixture and cement grout. This special structure granted SFP superior strength and durability and made it a promising solution for the paving of heavy trafficked area. This paper performed in-depth study on the mechanistic behavior of SFP. Firstly, the volumetric mix design of SFP was introduced, and followed with strength, moisture susceptibility, viscoelastic behavior, fatigue life as well as rutting resistance through a series of labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…It was also found in the previous study [45,46]. Li et al [7] revealed that the final rutting depth in the optimum SFP mixture was less than 2.5 mm. The researchers used cylindrical samples that were partially submerged in water in their investigation.…”
Section: Results and Discussion 41 Indirect Tensile Strength And Tens...supporting
confidence: 73%
See 1 more Smart Citation
“…It was also found in the previous study [45,46]. Li et al [7] revealed that the final rutting depth in the optimum SFP mixture was less than 2.5 mm. The researchers used cylindrical samples that were partially submerged in water in their investigation.…”
Section: Results and Discussion 41 Indirect Tensile Strength And Tens...supporting
confidence: 73%
“…Semi-flexible pavement (SFP) also known as grouted pavement, is a hybrid pavement that combines the properties of flexible and rigid pavement and is commonly used in various transportation infrastructure projects [7]. It consists of a porous asphalt mixture (PAM) with a 25-35% void ratio injected with cementitious grout material [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although various test methods are available for validating the relaxation modulus, the intricacy and challenges associated with the relaxation test process render it an incomplete measure of the viscoelastic characteristics of asphalt mixtures [23][24][25]. To address this limitation, this study ascertains the relaxation modulus of PSFM through dynamic modulus testing, employing the principle of time-temperature superposition [26][27][28]. This method involves the transformation of frequency domain-dynamic modulus relationship curves into time domain-relaxation modulus principal curves expressed using the Prony series.…”
Section: Introductionmentioning
confidence: 99%
“…These test sections have proved that road performance of the semi-flexible material was excellent [14]. At present, the research on semi-flexible pavement materials mainly focuses on the mix design of matrix asphalt mixture and high-performance cement grouting material [15][16]. In general, the volume method is used for the gradation design of matrix asphalt mixture, and the optimal asphalt-stone ratio is determined by drainage and scattering tests.…”
Section: Introductionmentioning
confidence: 99%